Understanding the experiences of residence hall custodians - Peterson, Rebecca (My University, 2026)
This qualitative research study explored the experiences of residence hall custodians at public 4-year institutions located within the Midwest. The study focused on participants’ interactions, motivations, training, and expectations related to their work as a custodian in the residence halls. The following research questions framed this study: (1) How do residence hall custodians describe the ways in which they interact with the students living in the buildings where they work?, (2) How do residence hall custodians describe their motivation to support students?, and (3) How do residence hall custodians describe the training and/or expectations that are provided by the custodial supervisory staff regarding relationship building with students? The research methodology used an interpretive study where 14 custodians participated in semistructured in-person interviews and a walk-through of their work areas. Photographs were captured during the walk-throughs, and relevant documents were provided. Analysis of the interviews, photographic memos, and documents allowed four themes to emerge from the data analysis: (a) Adaptive Practices and Unacknowledged Labor, (B) “I’m Here for the Students, (C) Community Contributions While Being Seen and Valued, and (D) “I Think the Building Would Probably Have Trouble Sticking Together If We Weren’t Here.” The findings suggest a disconnect between the work custodial staff provide in addition to cleaning and the mismatch between employee experiences and supervisor expectations. The findings enhance understanding of how custodial staff articulate their interactions with students and their motivations for engaging with residents. Understanding the experiences of an often-understudied population helps elevate the voices of campus service workers while helping to identify and understand their contributions to the campus enterprise.
Keywords: Custodian; Residence hall; Higher education; Student support; Web of inclusion